Feasibility study and evolutions of virtual CIM industry - Jiang, Haiping (2008)
The study defines Virtual CIM as CIM information sharing and business process collaboration within a company, between a company and its business partners and customers for the integration of total manufacturing enterprise through the use of Internet technologies and integrated systems.